Decreasing or increasing heat shock protein 72 exacerbates or attenuates heat‐induced cell death, respectively, in rat hypothalamic cells. Issue 1 (3rd September 2015) - Lin, Kao-Chang; Lin, Hung-Jung; Chang, Ching-Ping; Lin, Mao-Tsun
Abstract : Heat shock protein (HSP) 72 in serum was decreased to a greater degree in patients with serious heat stroke than in those with mild heat stroke. Thus, increased levels of HSP72 appeared to correlate with a better outcome for the patient. Nevertheless, the function of HSP72 in the heat‐induced hypothalamic cell death has not been assessed. In this study, we found that increasing HSP72 levels with mild heat preconditioning or decreasing HSP72 levels with pSUPER plasmid expressing HSP72 small interfering RNA significantly attenuated or exacerbated heat‐induced cell death in cultured primary hypothalamic cells, respectively. Our findings suggest that HSP72 plays a pivotal role in heat‐induced cell death and may be associated with heat tolerance. Abstract : Mild heat preconditioning up‐regulated HSP72 expression in cultured hypothalamic cells. siRNA‐HSP72 pretreatment down‐regulated HSP72 expression. Mild heat preconditioning attenuated heat‐induced cell loss. siRNA‐HSP72 pre‐treatment exacerbated heat‐induced cell loss. A positive correlation between HSP72 expression and heat tolerance might exist in hypothalamic cells.